Growth and developmental effects of DNA cytosine demethylation in two populations of the non-model species Geranium lucidum (2021)
Epigenetics is defined as the study of heritable changes in gene expression and function without being associated with any alteration of the underlying DNA sequence. Epigenetic mechanisms are quite sensitive to environmental stimuli, thereby they may provide a second system of heritable variation for natural selection to act upon. In plants, DNA methylation usually addresses ecological and evolutionary processes such as phenotypic plasticity and transgenerational effects. A suitable technique used to dissect the contribution of this epigenetic mark on those processes is the experimental DNA demethylation since it can be applied to both model and non-model species. In this study, we compare two experimental demethylation protocols on the non-model species Geranium lucidum, a noxious and invasive herb, to determine which of them is more efficient in removing DNA methylation marks, as well as altering growth and developmental phenotypes. Seeds from two geographically separated populations were subjected to two distinct demethylation protocols (seed germination and leaf infiltration). Leaf infiltration proved to be the most suitable protocol to reduce methylated DNA, while the germination protocol was unable to alter methylation levels. However, both treatments were unable to induce significant changes in the plant's phenotype. In conclusion, leaf infiltration is the best protocol to carry out future epigenetics research in this non-model species.